Pengaruh Current Ratio (CR), Debt To Equity Ratio (DER), Total Asset Turnover (TATO) Dan Returnon Equity (ROE) Terhadap Laba Bersih Pada Industri penyedia Jasa Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2017 - Ria Novika (Universitas Batanghari Jambi, 2019)
Net income and capital growth fluctuating in Telecommunication Industry can affect the return on equity (ROE). The existence of trend decline in profits that are not pursued its increase will affect the survival of the company. Important factors to measure the ability of the company are Current Ratio, Debt Equity Ratio, Total Asset Turnover and Return On Equity. In general, the success of a company in carrying out its activities are often based on the level of earned income.Telecommunication industry is one of the most competitive and rapidly growing business industries. Communication is not only used as a means of exchanging messages from a communicator to the communicant also to interact and connect between someone with other people.Result SPSS 20 gets the equation Log Y = 2,133 + 1,526 X1 + 0,781 X2 + 2,939 X3 - 0,187 X4 + e. In others words, the current ratio (X1), debt to equity ratio (X2), total asset turnover (X3), dan return on equity (X4) is able to explain the variable net income at industry telecommunication for the period 2012 – 2017 93,4% otherwise 6,6% be caused by other variables outside variables studied.Based on the test results simultaneously known that together there is influence that significant between the current ratio (X1), debt to equity ratio (X2), total asset turnover (X3), dan return on equity (X4) to net income at industry telecommunication period 2012 – 2017.